Pengembangan Manajemen Kurikulum Digital untuk Meningkatkan Mutu Perguruan Tinggi - Ashari, Alya; Arismunandar, Arismunandar (Indo-MathEdu Intellectuals Journal, 2025)
Digital curriculum management is the process of developing, implementing, and evaluating curriculum that utilize technology to improve the flexibility, efficiency, and relevance of learning in higher education. This study aims to analyze the role of digital curriculum management in improving the quality of higher education by using technology. Using a literature review method, the research subjects included scientific journals, books, research reports, and education policies related to curriculum digitization. Data were collected through content analysis techniques. The results of the discussion show that curriculum digitization can strengthen collaboration and data integration in the academic process by using digital platforms, LMS, and learning analytics. The use of this technology helps improve the suitability of materials to industry needs and supports data-driven decision making. However, its implementation still faces challenges related to educator readiness, infrastructure, and institutional policies. Overall, digital curriculum management has the potential to create a more adaptive and higher-quality learning ecosystem, while also increasing the competitiveness of graduates in the era of digital transformation.